2018
DOI: 10.1111/jdv.15204
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milk consumption on acne: a meta‐analysis of observational studies

Abstract: This meta-analysis provides evidence of a positive association between milk consumption and acne risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
(91 reference statements)
1
23
0
8
Order By: Relevance
“…Three studies also suggested that milk intake may increase the risk of more severe acne [40][41][42] , which is consistent with a meta-analysis that reported that high milk consumption was significantly associated with the presentation of moderate-severe acne 43 . Explanations for the association between milk intake and acne presentation may also explain the association observed for milk intake and acne severity.…”
Section: Parameters That Differ Between Control and Casesupporting
confidence: 79%
“…Three studies also suggested that milk intake may increase the risk of more severe acne [40][41][42] , which is consistent with a meta-analysis that reported that high milk consumption was significantly associated with the presentation of moderate-severe acne 43 . Explanations for the association between milk intake and acne presentation may also explain the association observed for milk intake and acne severity.…”
Section: Parameters That Differ Between Control and Casesupporting
confidence: 79%
“…Increased height and BMI during puberty correlates with a higher incidence of acne vulgaris [259][260][261][262], the most common inflammatory skin disease in industrialized countries, pointing to common accelerated growth trajectories in acne pathogenesis. The relationship between cow milk consumption and acne has been confirmed by recent meta-analyses [263][264][265]. In contrast, lactose-intolerant individuals, who generally avoid milk, exhibit a 50% lower frequency of acne compared to lactose-tolerant people [266].…”
Section: Acne Vulgarismentioning
confidence: 81%
“…In these studies, the relationship between glycemic index-based food con- sumption and AV has been investigated mostly regarding fish meat, milk/dairy products, and chocolate. [20][21][22] There are conflicting results in different studies on the effect of BMI on AV development as in certain other skin diseases. [23][24][25][26] In this study, there is no statistically significant difference in mean BMI between the patients with AV and the control group.…”
Section: Discussionmentioning
confidence: 99%